Removal of Inorganic Contaminants Using Manufacturing Porous Media - Salman Muhsun, Sadiq; Rashid Gubashi, Karim; Fahim Chyad, Rawaa; T. Al-Sharify, Zainab (International Journal of Engineering and Technology, 2018)
The objective of the experimental work performed in this study is to analyze the adsorption of the total organic carbon from aqueous solutions using a manufacturing porous media of Activated Ceramic (ACR) in a continuous flow system, consisting of horizontal PVC pipes of 150 mm diameter and 6 m length without membranes. The discharge of the polluted water in the system was varied at values of 10, 20, 40, 60, 80 and 100 L/hr while the contaminants were changed in concentrations of high and low with the measurement of pressure. The results show that in order to increase the removal efficiency of heavy metals, the detention time and the length of the pipe must be increased. The decrease in flow discharge results in an increase in the removal efficiency of the heavy metals while the results for the removal process of the ACR media were: Mn+2> Cr+3 > Fe+2 > Cu+2 > Zn+2.Â Â